Biomedicine Potential of Oil Palm (Elaeis guineensis) Leaves: In Vitro Evaluation of Antibacterial, Antibiofilm, and Antioxidant Activities - Setiawan, Deni; Hadi, Samsul; Mahdi, Nur; Mardiati, Nurul; Dwi Sandi, Dita Ayulia; Ridha, Muhammad Rasyid; Bachri, Moch. Saiful (Universitas Borneo Lestari, 2026)
Oil palm (Elaeis guineensis) leaves possess diverse pharmacological properties with promising development potential, particularly as antibiofilm and antioxidant agents. This study aimed to evaluate the antibacterial, antibiofilm, and antioxidant activities of E. guineensis leaf extract. The leaves were macerated in acetone for five days. Antibacterial activity was determined using the disc diffusion method against four bacterial species: Staphylococcus aureus, Propionibacterium acnes, Escherichia coli, and Pseudomonas aeruginosa. The extract exhibited moderate antibacterial activity, with the highest inhibition observed against P. acnes (6.79 mm at 25%). Antibiofilm activity was evaluated using a microdilution method, showing concentration-dependent inhibition, with the highest activity at 1% concentration, reaching 83.90% (mid-phase, S. aureus) and 71.28% (E. coli). Antioxidant activity was assessed using DPPH, FRAP, and ABTS assays, yielding IC50 values of 99.19 ppm, 119.12 ppm, and 123.37 ppm, respectively, indicating moderate antioxidant capacity (IC50 > 50-150 ppm). Overall, E. guineensis leaf extract demonstrates moderate antibacterial, antibiofilm, and antioxidant activities, suggesting its potential as a preliminary candidate for further pharmacological investigation.